The consent to a clinical trial of who cannot consent: ethics facing GCP - Bignamini, Bignamini (Medicina e Morale, 1999)
The consent to a clinical trial of who cannot consent marks the crossing point of four alternatively substantial or formal conditions: a) ethically, or legally, correct position; b) information and consent , or consent documentation; c) physical, or technical, impossibility; d) acts which are, or are not, in the direct patient's interest. The Good Clinical Practice (GCP) anticipates four conditions of incapacity: 1. Is unable, or cannot, read and write; 2. minor of age or legally incapable but with real capacity; 3. minor of age or legally incapable without real capacity, or unconscious, with legally acceptable representative; 4. minor of age or legally incapable without real capacity, or unconscious, without legally acceptable representative. The GCP anticipates specific procedures for these circumstances, which might however be ethically not acceptable and result in contrast with the ethics committee. The GCP considers indeed equivalent subject and representative, what may be acceptable for therapeutic studies, but is not acceptable for non-therapeutic trials. When the incapacity to consent is only formal, there is no substantial contrast between GCP and ethics, provided that the information is complete and there is actual freedom to consent. The ethics committee will concentrate on these aspects. When the incapacity to consent is substantial, the ethics committee and the investigating physician could reject formally GCP-compliant protocols, on binding ethical ground. They are indeed bound to operate under the specific conditions of emergency medical acts, having as inescapable condition the presumable direct patient's interest.